2020
DOI: 10.1111/jpc.15138
|View full text |Cite
|
Sign up to set email alerts
|

Communication between parents and well‐siblings in the context of living with a child with a life‐threatening or life‐limiting condition

Abstract: Effective parent-child communication may serve to buffer the potential negative impacts of stressful situations on a child. Children who have a brother or sister with a life-threatening or life-limiting medical condition may turn to their parents for help with comprehending the situation, to help maintain their own ability to function across various life areas or to receive emotional support. There is a need for more investigation into the nature and importance of parent-child communication in the context of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Our results further showed that siblings wanted to know that they had someone to talk with, be informed about the ill child’s illness status, and have moments of rest. The importance of talking with someone is consistent with other studies reporting that communication between parents and siblings is one of the most critical factors in siblings adapting to life with an ill child (Jaaniste et al, 2020 ; Marklund et al, 2018 ), and leading to siblings feeling less alone (Eaton Russell et al, 2018 ; Lövgren et al, 2020 ). Siblings may struggle to speak about their feelings (Jaaniste et al, 2022 ) or avoiding initiating conversations to protect their parents from feeling sad or uncomfortable (Eaton Russell et al, 2018 ).…”
Section: Discussionsupporting
confidence: 85%
“…Our results further showed that siblings wanted to know that they had someone to talk with, be informed about the ill child’s illness status, and have moments of rest. The importance of talking with someone is consistent with other studies reporting that communication between parents and siblings is one of the most critical factors in siblings adapting to life with an ill child (Jaaniste et al, 2020 ; Marklund et al, 2018 ), and leading to siblings feeling less alone (Eaton Russell et al, 2018 ; Lövgren et al, 2020 ). Siblings may struggle to speak about their feelings (Jaaniste et al, 2022 ) or avoiding initiating conversations to protect their parents from feeling sad or uncomfortable (Eaton Russell et al, 2018 ).…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the qualitative literature in this field, documenting perceptions that friends do not understand what they are going through (Løkkeberg et al, 2020). Although the protective effects of familial support are likely to be multifaceted, arguably, a central component is likely to be effective familial communication, including information sharing, problem‐solving and providing emotional support (Jaaniste et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Parents often take on significant healthcare roles within their family including administering medication, case management, using assistive technology, and cleaning/providing ongoing maintenance of health equipment (Caicedo, 2014). Caregiving for children with complex health needs is time-consuming, physically arduous, and highly stressful (Caicedo, 2014; Jaaniste et al, 2020; McCann et al, 2012). Caregivers of children with medical complexity report a median of 2 h per week providing care coordination and over 11 h a week providing direct home care (Kuo et al, 2011).…”
Section: Raising Children With Complex Care Needsmentioning
confidence: 99%
“…Repeated exposure to severely stressful medical procedures can activate an infant or child’s stress response, thus increasing the potential for experiencing long term trauma as a result of ongoing and sustained medical treatments. Second, siblings of children with medical complexity have been shown to have increased risk of negative emotional, social, and academic outcomes (Jaaniste et al, 2020; Tay et al, 2021). The psychological and social well-being of siblings of medically complex children is threatened by ongoing stress, lack of support by parents, and intrusive lack of family stability (Incledon et al, 2015; Jaaniste et al, 2020).…”
Section: Raising Children With Complex Care Needsmentioning
confidence: 99%
See 1 more Smart Citation